Integrating Augmented Reality in Storage Technology Learning Module (ARStore) - Ramli, Azira Raihan; Ali, Azita; Ismail, Affero (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract:The importance of innovation in technology has led to various uses in all fields including education. The integration of this technology in education always opens new opportunities for students to have a new learning environment in a subject they learnt, especially for university students. One of the technology  that have been integrated in education is Augmented Reality (AR). This study aims to plan and develop the teaching and learning module with the integration of AR technology. The combination of multimedia elements and 3D models will be able to attract students in the teaching and learning process. The development of this game application was developed by Unity software as the main platform, Adobe Illustrator to design icons and buttons for applications and Vuforia for AR parts. In order to develop the application systematically, the developers use the Hybrid ADDIE as development methodology. Expert review and functionality test had been done during the evaluation phase and the results show that the experts agree that ARStore fulfills all the required functions. It is hope that this module can be used for student to learn this subject and the idea can be expend for the use in other subject. Keywords: AR, Multimedia, Module Learning, Data Storage